LA INEXISTENCIA DE LA DECLARATORIA DE INSOLVENCIA EN EL CÓDIGO ORGÁNICO GENERAL DE PROCESOS - Granillo Ordóñez, Manolo Andrés (2019)
The present thesis entitled: "The non-existence of the declaration of insolvency in the General Organic Code of Processes", refers to the lack of insolvency declaration for debtors who have failed to cure the creditor, fulfilling the execution order issued in judgment by the competent authority. The lack of assets to be able to ensure payment, leaves a lack of a guarantee capable of recovering the credit, generating legal uncertainty and its detriment to creditors. The non-payment of the credit given by the creditor towards the debtor, reaches a stage in which it ends up harming third parties, given that the declaration is not properly said, dictated or resolved by a superior. In the same way, since the competent authority to issue and execute the insolvency is not established, the rights of the creditors are being left in complete vulnerability because they cannot collect the obligation, which should be fulfilled according to the law. execution order and payment agreement agreed upon when acquiring the obligation. Therefore, the fulfillment of the obligation must go according to the execution title, demonstrating the need to proceed with the immediate declaration of insolvency of the debtor party.